2020
DOI: 10.1186/s12866-020-01781-z
|View full text |Cite
|
Sign up to set email alerts
|

Design of PCR assays to specifically detect and identify 37 Lactobacillus species in a single 96 well plate

Abstract: Background: Lactobacillus species are used as probiotics and play an important role in fermented food production. However, use of 16S rRNA gene sequences as standard markers for the differentiation of Lactobacillus species offers a very limited scope, as several species of Lactobacillus share similar 16S rRNA gene sequences. In this study, we developed a rapid and accurate method based on comparative genomic analysis for the identification of 37 Lactobacillus species that are commonly used in probiotics and fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…However, these genera mostly comprised non-pathogenic species. Several studies have demonstrated that the accuracy of PCR assays using appropriate primers for bacterial identification at the species level [ 69 , 70 ]. The PCR analysis revealed that only S. aureus was detected in one sample.…”
Section: Discussionmentioning
confidence: 99%
“…However, these genera mostly comprised non-pathogenic species. Several studies have demonstrated that the accuracy of PCR assays using appropriate primers for bacterial identification at the species level [ 69 , 70 ]. The PCR analysis revealed that only S. aureus was detected in one sample.…”
Section: Discussionmentioning
confidence: 99%
“…However, because several phylogenetically closely related novel L. plantarum group species have been proposed in recent years [ 7 , 8 ], the usability and specificity of recA gene–based PCR and sequencing as well as species-specific primers should be reassessed through in silico methods. To identify highly distinguished taxonomic markers with deep-level phylogeny or species-specific genes according to the gain and loss of variable regions, the use of genome comparison methods have been applied to resolve the phylogenetically and phenotypically closely related species; this serves as an alternative to the conventional universal phylogenetic targets [ 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, genes such as 16S rRNA, 16S-23S rRNA intergenic spacer region, and the elongation factor Tu (tuf) gene have been used to distinguish microorganisms at the species or subspecies level [4,9,[26][27][28][29]. However, some studies have reported that these genes share high sequence similarities without showing sufficient variabilities to allow for the differentiation between L. delbrueckii subspecies [4,13]. In contrast, we selected genetic markers specific to the genomes of each subspecies using pangenome analysis.…”
Section: Genetic Marker Specificity Testmentioning
confidence: 99%